Tubular bimetal oxysulfide CuMgOS catalyst for rapid reduction of heavy metals and organic dyes. (26th February 2019) - Chen, Xiaoyun; Kuo, Dong‐Hau; Zhang, Jubin; Lu, Qingxin; Lin, Jinguo; Liao, Yiqiang
Abstract : Tubular bimetal oxysulfide Cu Mg OS catalyst was prepared using a feasible method at a low process temperature of 95°C. X‐ray diffractometry, X‐ray photoelectron spectrometry, field emission‐scanning electron microscopy, transmission electron microscopy, UV–Vis diffuse reflectance spectroscopy, photoluminescence emission spectrum, and nitrogen adsorption–desorption isotherms were used for Cu Mg OS characterizations. The Cu Mg OS reduction activities were investigated through the reduction of heavy metals of Cr (VI), Pb (II) and Hg (II) solutions, and the organic dyes of rhodamine‐B (RhB), methyl orange (MO) and methylene blue (MB) solutions under dark. The results showed that the Cu Mg OS prepared with an appropriate N2 H4 amount for a suitable Cu (I)/Cu (II) ratio exhibited fast reduction activity without adding any reagents, with which the 100 mL Cr (VI), Pb (II) and Hg (II) solutions of 50 ppm were 100% reduced by 20 mg Cu Mg OS within 4 min, 6 min and 4 min, respectively. The 100 mL RhB, MO and MB solutions of 50 ppm were 100% reduced by 10 mg Cu Mg OS within 4 min, 5 min and 1 min, respectively, under the existence of NaBH4 . Cu Mg OS displayed excellent chemical stability for the re‐use tests on heavy metal ions and organic dyes. The excellent performance is attributed to Cu Mg OS bimetal oxysulfide catalyst with active surface reaction centers to interact with reactants, and the carrier hopping between Cu (I) and Cu (II). Abstract : Tubular bimetal oxysulfide Cu Mg OS catalyst prepared with an appropriate N2 H4 amount for a suitable Cu (I)/Cu (II) ratio exhibited fast reduction of heavy metal ions and organic dyes. The excellent performance is attributed to Cu Mg OS with surface reaction centers to interact with reactants, and the carrier hopping between Cu (I) and Cu (II).